2006
DOI: 10.1016/j.mod.2006.01.001
|View full text |Cite
|
Sign up to set email alerts
|

fused regulates germline cyst mitosis and differentiation during Drosophila oogenesis

Abstract: The fused gene encodes a serine-threonine kinase that functions as a positive regulator of Hedgehog signal transduction in Drosophila embryogenesis, wing morphogenesis, and somatic cell development during oogenesis. Here, we have characterized the germline ovarian tumors present in adult ovaries of fused mutant females, a phenotype not observed upon deregulation of any other component of Hedgehog signaling. In the strongest fused mutant contexts, we found that tumorous ovarian follicles accumulate early spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 56 publications
(40 reference statements)
2
11
0
Order By: Relevance
“…Hence, ectopic activation occurs cell autonomously, but is induced by the Dpp ligand. The ectopic activity induced by loss of fu function causes a variety of phenotypes, including egg chambers that contain 32 GCs, as we have observed upon loss of lgd function here (Narbonne-Reveau et al, 2006). We have previously shown that loss of function of lgd results in a defect in the degradation of Tkv and other cargo proteins, such as Notch and Dl, in FCs and GCs (Jaekel and Klein, 2006).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Hence, ectopic activation occurs cell autonomously, but is induced by the Dpp ligand. The ectopic activity induced by loss of fu function causes a variety of phenotypes, including egg chambers that contain 32 GCs, as we have observed upon loss of lgd function here (Narbonne-Reveau et al, 2006). We have previously shown that loss of function of lgd results in a defect in the degradation of Tkv and other cargo proteins, such as Notch and Dl, in FCs and GCs (Jaekel and Klein, 2006).…”
Section: Discussionsupporting
confidence: 64%
“…The phenotype of lgd in the germline resembles that of fu mutants (Narbonne-Reveau et al, 2006). Therefore, we tested whether lgd and shrub have a functional relationship with fu.…”
Section: Functional Interactions With Fu During Germline Developmentmentioning
confidence: 92%
See 1 more Smart Citation
“…In contrast, the number of TA division was not sensitive to defects in fu . Because null fu mH63 / Y mutants failed to survive to adulthood, the numbers of spermatocytes in single cysts were examined in testes from adult male flies carrying fu 50 , a viable allele that exhibits the strongest germline tumor phenotype in ovary that is resulting from hyperactivation of BMP signaling in cystoblasts (Narbonne-Reveau et al, 2006). Consistent with our finding that fu was not essential for downregulation of pMad in early germ cells during testis development, 32-cell cysts were not observed in fu 50 testes (lane 7 in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Given that previous studies demonstrated that the Hh pathway is not required in germline cells, and the loss-of-function of Fu leads to early germ cell proliferation 43 , the mechanism of Fu activation in the germline might be different and Hh independent. Our data indicate that Fu forms a dimer in response to Hh through Cos2/Smo interactions; the formation of a Fu dimer is Smo- and Cos2-dependent and is regulated by both graded Hh and the graded phosphorylation of the Smo C-tail.…”
Section: Discussionmentioning
confidence: 99%